Experimental investigation of the protective effect of wind barriers on high-speed railway bridge in inland strong wind area. Issue 15 (November 2019) - Ren, Wanmin; Duan, Qingsong; Ma, Cunming; Liao, Haili; Li, Qiusheng
This study aims to investigate the wind protective effect of wind barriers on the Lanzhou–Xinjiang high-speed railway using wind tunnel tests. Wind barriers with different heights and porosities were analyzed. Two girders, that is, a box-girder and a trough-girder, each with 1:30 and 1:8 scales were experimentally investigated. The results suggest that the protective effect of the wind barrier with a height of 4 m and porosity of 20% is better than the others. The influence of wind barriers on the aerodynamic characteristics of train vehicles and girders must be analyzed simultaneously. The aerostatic force coefficients of trains are approximately the same at different scales, and the Reynolds number effect could be neglected.